Educação natural, antropologia e sociabilidade no Emílio de Rousseau - Pokojeski, Sueli (2008)
The perspective of the Natural Education bases the pedagogical tradition of Emilio delineating the different stages of the human development. This study it focused the human development that understands the age of the reason and passions, that constitutes the character of the human being. In book IV of Emilio, Rousseau formulates the thesis of that socialization human manifest human if by means of the confrontation of the two human feelings, the love of itself and the proper love. Such confrontation supports the development of the individual being that, knowing its feelings, it can know and it respects itself and the others. Rousseau values in this book, the infancy of the child as one of the basic points of the prolongation of the learning, which will affect the adult life, e will confer it support and capacity to face definitive challenges, not only personal, as well of the social environment. It is armed, then, of importance, its thought, in uncurling of the relation between individual and society, in the construction of the contract as a form to mediate the social, cultural and educational relations